(untitled) (Research, Society and Development, 2021)
The antimicrobial activity of Caryocar brasiliense and Annona crassiflora leaves extracts was evaluated against Escherichia coli strains through a sensitivity test by the agar diffusion method and by the evaluation of minimal inhibitory concentrations (MIC) and minimal bactericidal concentrations (MBC) by the microdilution technique followed by plating. The sanitizing efficiency of these extracts in reducing E. coli cells biotransferred from L. sativa leaves to polypropylene surfaces was evaluated after an exposure time of 5 minutes. All strains were sensitive to antibacterials and the formation of an inhibition halo was observed for the extracts against all strains tested. The C. brasiliense extract showed better antimicrobial action against E. coli strains, with a MIC of 1.09 mg/mL, while the MIC of A. crassiflora extract was 5.58 mg/mL. No MBC was found for plant extracts. The strains were not able to form biofilms under the conditions studied, however, there was biotransfer and adhesion of E. coli to polypropylene. The highest counts of E. coli cells biotransferred and, consequently, adhere to the polypropylene coupons were observed when 5 log CFU/mL was inoculated, with a mean count of 4.53 ± 0.66 log CFU/cm2. It was verified that the treatment with the extract solutions in the minimum inhibitory concentrations (MIC) totally reduced the number of E. coli cells adhered to the polypropylene coupons. The results obtained indicate that the use of extracts from both species as antibacterials is promising.